PENGARUH KECERDASAN INTELEKTUAL (IQ), KECERDASAN EMOSIONAL (EQ), KECERDASAN SPIRITUAL (SQ) TERHADAP KINERJA PEGAWAI INSPEKTORAT PROVINSI KALIMANTAN SELATAN - Hari Nugroho Akimas; Ahmad Alim Bachri (JWM (JURNAL WAWASAN MANAJEMEN), 2016)
This Research is to analyze the effect of Intellectual Quotient (IQ), Emotional Quotient (EQ), and Spiritual Quotient (SQ) to the employee performance of Inspectorate South Kalimantan Province. All of The employee are involved as the samples, 81. Data are the perception of the employee regarding the variables. Technique of analysis is using multiple linear regression. Tests involved are Model Test (F), t Test, and classic Assumption test. Significant Test is connected to pvalue. The results show that (1) Intellectual Quotient (IQ) is influencing insignificantly to the employee performance; (2) Emotional Quotient (EQ) is influencing insignificantly to the employee performance; (3) Spiritual Quotie nt (SQ) is influencing significantly to the employee performance. The results also indicate that such effects need further research. Variables should be considered are attitude, operating standar and Technology.